The effect of Equilume light masks on the timing of seasonal ovulation of Thoroughbred mares in South Korea - Gaeun Lee; Heejun Jung; Minjung Yoon (The Korean Society of Animal Reproduction and Biotechnology, 2020)
Advancing the estrous cycle of mares is an essential breeding strategy that is routinely conducted by Thoroughbred breeders to improve economic outcomes. For this purpose, Equilume light masks have been developed as an alternative to existing technologies such as artificial lighting or hormonal treatments because they are considered as valid as existing methods with additional animal welfare advantages. For example, with the Equilume light masks, horses can be let out into the pasture, whereas they have to be kept indoors during lighting treatment. Because the function of Equilume light mask on the estrous cycle of mares is influenced by environmental factors such as nutrition condition and temperature, Equilume light mask should be studied in various environments. The objective of the present study was thus to verify the effect of Equilume light masks on the onset of the estrous cycle in Thoroughbred mares in South Korea. Mares were randomly selected and separated into two groups at two Thoroughbred horse breeding farms. The mares in the treatment group were equipped with Equilume light masks from November 18 to February 10 the following year. The body condition, the number and size (> 35 mm) of uterine follicles, and the uterine horn score of the mares were assessed on January 6 and February 10. The body condition scores were not different between the two groups. The treatment with the Equilume light mask had no positive effects on developing follicles and the reproductive tract. In conclusion, the use of Equilume light masks did not influence the seasonal resumption of the estrus cycles in Thoroughbred mares in South Korea.